FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERAWAT DI INSTALASI RAWAT INAP RSUD SAWAHLUNTO - Desrison, Desrison; ratnasari, Sri langgeng (University of Riau Kepulauan, 2018)
Human resources like the nurses as a integral parts from medical services, have big contribution to select medical services at hospital. The nurses at hospital are a main point medical services, couses that human resources that contain the biggest and most interaktif with client continously and balance to give comprehensives medical services and professional reactions. The research purposing to know the factors that connected with styling work grade of nurses. The research do at resting installation RSUD, Sawah Lunto. The factor that observe are royalty grade, education grade, and leader grade. The research design that using is cross sectional, data proses and analyzes with using computerization program SPSS for window version 11.0 with Chi Square Test. The research populations are all nurses that have duty at resting room RSUD, Sawah Lunto in surgical operation, child room, and midwife services, that amount are 56 people, and all of population be a sample. From result research get 51,8% styling work from the nurses is like usual not the best. Statistic result show that relationship between motivations, salary, and leadership wit styling work, at the other side education grade not show relationship wit styling work. According the observation, the nurses more add motivation at working, officer at hospitas must attract nurses incentives and head officer more add activity and controlling to the working nurses.